Estudo da hidrólise enzimática do soro de queijo utilizando as lactases Lactozym® e Prozyn® - Vieira, Aline Alves Melo Tostes (2006)
The study of the enzymatic hydrolysis of the lactose has been of great importance, due to absence or lack of the enzyme present lactase in the process digestive human. The enzyme β-galactosidase is very used in the processing of milk products by being of low cost and enough studied all over the world. The use of this enzyme in the dairy products prevents the crystallization of the products and it provides to the intolerant people the lactose better life quality. The objective of this work was accomplish a comparative study of the hydrolysis of the cheese whey usig two different maufactures β-galactosidase Prozyn and Lactozym, respectively, Kluyveromyces lactis and Kluyveromyces fragilis, of origin of yeasts. The tests of hydrolysis of the cheese whey were accomplished in a reactor with agitation control and temperature. The cheese whey concentration was of 60 g/L, temperatures of 43, 45 and 48°C, concentration of the enzyme of 4 g/L, pH 6,0 and 6,5 and agitation 300 rpm. Both enzymes obteined better result to 45 °C, however the enzyme Prozyn converts the lactose in smaller time. An analysis was accomplished to verify the concentration of total sugar of the cheese whey, 75%, to evaluate the hydrolysis, obtaining the glucose concentration in function of the time for each studied condition. The influence of the lactose concentration was verified in the enzyne, using lactose solution in erlenmeyer. The enzymatic activity was growing of the concentration 10 g/L up to 120 g/. The enzyatic stability in relation to the pH presented better result pH 6,5 for both enzymes Prozyn and Lactozym. The thermal stability of the free enzyme was certain for the time of half life. The enzyme Prozyn to temperature of 50°C it presented time of life 4,62 min and to 55°C was 2,77 min and enzyme Lactozym to the 50°C was 6,32 min and to 45°C was 115,52 min. In the determination of the enzymatic activity the method of the initial rates of the reaction of hydrolysis of the cheese whey was used. The obteined enzymatic activity was 75,03.10-3 mol/(genzyme.h) and 44,6.10-3 mol/(genzyme.h) for Prozyn and Lactozym, respectively.